The Oath in the ОТ in the Light of Related Terms in the Legal and Covenantal Context of the Ancient Near East - Magnetti, Donald L.
Dissertation; Microfilm $3.20; Xerox $11.25. Cf. Dissertation Abstracts 30 (1969-70) 689-A. 7.